Philippe Lejeune, Catherine Bogaert: Historia pewnej praktyki „Uri journal à soi" (Paris 2003, Ed. Textuel, s. 214, album) - Lubas-Bartoszyńska, Regina (Przestrzenie Teorii, 2007)
This article discusses the content of an album of P. Lejeune and C. Bogaert, published in Paris in last year (in 2003), dedicated to a personal diary. The fact of bringing out of this publication became for the author of this article an impulse to present an anthropological view at the form of diary. The author - taking an opportunity of presenting the content of the album - gives an outline of the tradition of the genre, discusses various criteria (geographical, historical, sociological) which have an influence on the development and formation of this literary form. The author also draws attention to the significant features of a personal diary (the ones which differ it from, e.g. autobiography) and its kinds (from the purest form of a personal, intimate diary through the diary-letter written by one to him/herself to some unconvetional diaries such as: a painter's diary, diary-comic-strip, film diary, diary-photograph, on line diary - blog). While also pointing to such forms as: spiritual diaries, journey diaries, log books, and historical chronicles, the author emphasises the necessity of relating the origin of the diary with a concrete situation of men.